2006
DOI: 10.4314/gmj.v40i2.36016
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal cancer at the Korle Bu Teaching Hospital, Accra, Ghana

Abstract: We conclude that significant number of patients with laryngeal cancer presented with locally advanced disease and dysphonia was the commonest symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
4
19
0
Order By: Relevance
“…In this study squamous cell carcinoma was identified in 90.3% of all the cases, whereas Kitcher et al (2006) reported of an incidence of 88.7%, Amusa et al (2011) identified 100% in their study and Iseh et al (2011) also identified 66.7%.…”
Section: Discusssionsmentioning
confidence: 46%
See 2 more Smart Citations
“…In this study squamous cell carcinoma was identified in 90.3% of all the cases, whereas Kitcher et al (2006) reported of an incidence of 88.7%, Amusa et al (2011) identified 100% in their study and Iseh et al (2011) also identified 66.7%.…”
Section: Discusssionsmentioning
confidence: 46%
“…Adenocarcinoma and adenoid cystic carcinoma were each identified in 2.1% of the cases whereas Kitcher et al (2006) also reported of an incidence of 1.7%. Olofsson andvan Vostrand (1977), Del Negro et al (2007), Zvrko and Golobović (2009) all reported of an incidence rate of less than 1.0% in their respective studies.…”
Section: Discusssionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Clinical manifestations of laryngeal carcinoma in adolescents may include hoarseness or cough, which may be mistaken for common respiratory infections, pre-pubertal voice change, or other benign childhood conditions 24 . Recurrent respiratory tract infection, or asthma, vocal abuse, difficult examination in children makes the case more aggressive and ultimately fatal 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that head and neck cancer is the eighth most common cause of cancer death worldwide [1]. la ryn geal cancer is one of the head and neck malignant tu mors that se riously lead to health damage.…”
mentioning
confidence: 99%